Rancang Bangun Sistem Informasi Wisata Kuliner di Kota Klaten Berbasis Web - Syahid, Hamdani Nur, Nurgiyatna, ST., MSc., PhD (2016)
Culinary tourism is now becoming a kind of tour is big impact on the development of an area, one importance is to cultivate potential food places in the area. In the City of Klaten own little is even rarer website devoted to informing and container to promote culinary places that are in an area, then it needs a system of online-based information associated with it. Design of information systems culinary tourism in the City of Klaten is a web-based information system that provides information and services for business travelers who want to promote the culinary place in internet media. In this information system includes a variety of information about culinary start point and the food menu is offered. This system uses waterfall method and system design using the design model UML (Unified Modeling Language). The system is built using the PHP programming language and MySQL database for storage use. The system uses the black box testing and testing of questionnaires to the public. Based on these tests, produce information systems places and culinary menu located in the City of Klaten so that the potential of culinary tourism in Klaten growing.